Polycystic ovary syndrome detection using neural network. - Istiyaq, Tahsin; Jahan, Nusrat; Diptho, Rakib Ahmmed; Anika, Fairuz; Sadakin, Sifat-E (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.